Cassava agronomy research in Asia: Has it benefitted cassava farmers? - Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2001)
During the past decade (1990-2000) the area planted to cassava in most countries in Asia has generally decreased, while production has remained stable or also decreased. Cassava yields have increased mainly in India, Indonesia and China but remained nearly the same in Malaysia, Thailand and the Philippines, and actually decreased in Vietnam. Yield stagnation or declines, inspite of widespread adoption of higher yielding varieties, is partly due to displacement of cassava to more marginal regions, and partly a result of the deterioration of the soil resources due to erosion and inadequate or unappropriate fertilizer use. The paper describes research results obtained in the development of improved cultural practices, such as time and method of planting, weed control, fertilization, intercropping and erosion control. Experiments have shown that cassava yields are seriously reduced if either low rainfall or low temperatures are limiting growth during the period of 3-5 months after planting; that planting vertically or inclined produces higher yields than planting horizontally, especially during periods of drought; that planting on ridges is better in the rainy season but planting on the flat is better in the dry season; that high yields can be sustained over many years of continuous cassava planting if adequate amounts of N and K are applied annually; that intercropping with peanut generally increases total income and protects the soil from erosion; and that fertilization, intercropping, contour ridging and contour hedgerows of grasses are very effective ways to reduce erosion. Areas in which additional research is needed are suggested. Improved cultural practices, such as the use of chemical fertilizers and herbicides have been adopted in some regions or countries, such as Tamil Nadu, Malaysia, Thailand (to some extent), Indonesia and south Vietnam (mainly fertilizers). Constraints to adoption are identified and policy changes are suggested that will enhance the adoption of better practices that will contribute to increasing the income of cassava farmers and maintaining or improving the productivity of the soil.